A novel approach for fibrous dysplasia assessment using combined planar and quantitative SPECT/CT analysis of Tc-99m-diphosphonate bone scan in correlation with biological bone turnover markers of disease activity - Jreige, Mario; Hall, Nicolas; Becce, Fabio; Aubry-Rozier, Bérengère; Gonzalez Rodriguez, Elena; Schaefer, Niklaus; Prior, John O.; Nicod Lalonde, Marie (Frontiers in Medicine, 2022)
Purpose: To investigate the emerging role of Tc-99m-labeled diphosphonate (Tc-99m-DPD) uptake quantification by SPECT/CT in fibrous dysplasia (FD) bone lesions and its correlation with biological bone turnover markers (BTMs) of disease activity. Materials and Methods: Seven patients (49±16 years) with a confirmed diagnosis of FD were included in this retrospective study. Bone scan with Tc-99m-DPD and quantitative SPECT/CT (xSPECT/CT) were performed. SUVmax (maximum standard unit value) and SUVmean (mean standard unit value) were measured in all FD bone lesions. The skeletal burden score (SBS) was assessed on planar scintigraphy and multiplied by mean SUVmax and SUVmean to generate two new parameters, SBS_SUVmax and SBS_SUVmean, respectively. Planar and xSPECT/CT quantitative measures were correlated with biological BTMs of disease activity, including fibroblast growth factor 23 (FGF-23), alkaline phosphatase (ALP), procollagen 1 intact N-terminal propeptide (P1NP) and C-terminal telopeptide (CTX), as well as scoliosis angle measured on radiographs. Statistical significance was evaluated with Spearman’s correlations. Results: A total of 76 FD bone lesions were analysed, showing an average SUVmax and SUVmean (g/mL) of 13±7.3 and 8±4.5, respectively. SBS, SBS_SUVmax and SBS_SUVmean values were 30.8±25.6, 358±267 and 220.1±164.5, respectively. Mean measured values of FGF-23 (pg/mL), ALP (U/L), P1NP (µg/L) and CTX (pg/mL) were 98.4 (22–175), 283.5 (46–735), 283.1 (31–1161) and 494 (360–609), respectively. Mean scoliosis angle was 15.7 (7–22) degrees. We found a very strong positive correlation between planar-derived SBS and CTX (r=0.96, p=0.010), but no significant correlation between SUVmax or SUVmean and biological BTMs. SBS_SUVmax showed a strong to very strong positive correlation with CTX (=0.99, p=0.002), FGF-23 (=0.91, p=0.010), ALP (=0.82, p=0.020), and P1NP (=0.78, p=0.039), respectively. Conclusion: This study showed that biological BTMs are significantly correlated with diphosphonate uptake on bone scan, quantified by a new parameter combining information from both planar and quantitative SPECT/CT. Further analysis of bone scan quantitative SPECT/CT data in a larger patient population might help better characterize the skeletal disease burden in FD, and guide treatment and follow-up.